A Putative Guanosine Triphosphate Cyclohydrolase I Named CaGCH1 Is Involved in Hyphal Branching and Fruiting Development in Cyclocybe aegerita - Tao, Nan; Cheng, Bopu; Chai, Hongmei; Cui, Xianghua; Ma, Yuanhao; Yan, Jinping; Zhao, Yongchang; Chen, Weimin (Frontiers in Microbiology, 2022)
GTP cyclohydrolase I (GCH1) is the limiting enzyme of the tetrahydrobiopterin (BH4) synthesis pathway. The disruption of gch1 gene may cause conditional lethality due to folic acid auxotrophy in microorganisms, although the function of gch1 in basidiomycetes has not been deciphered so far. In the present study, gch1 expression in Cylocybe aegerita (cagch1) was downregulated using the RNAi method, which resulted in growth retardation in both solid and liquid medium, with the hyphal tips exhibiting increased branching compared to that in the wild strain. The development of fruiting bodies in the mutant strains was significantly blocked, and there were short and bottle-shaped stipes. The transcriptional profile revealed that the genes of the MAPK pathway could be involved in the regulation of these effects caused by cagch1 knockdown, which provided a cue to study the role of gch1 in the development process of basidiomycetes.